Peran Bea Cukai dalam Penegakan Hukum terhadap Tindak Pidana Penyelundupan Bawang Merah - Zubaidi, Zaiyad; Eriyanti, Nahara; Fiani, Ade Nuzul (Tasyri' : Journal of Islamic Law, 2023)
This paper is motivated by the rise of criminal acts of smuggling of goods and services in Indonesia. The Customs and Excise Party as a government agency has conducted supervision and inspection of imports of goods both from within and from abroad to eradicate smuggling. The Sumatra region, one of which is the Aceh region, is one of the places for committing the crime of smuggling shallot products. If this crime always occurs every year, then every year the state suffers losses. This study used qualitative research methods. The data sources for this research are field data (field research) and literature (libray research). The results showed that the role of Langsa City Customs and Excise in law enforcement against the criminal act of smuggling shallots was by conducting patrols, strengthening intelligence and community information, carrying out law enforcement, collaborating with other agencies. Many obstacles were faced by the Customs and Excise of Langsa City in enforcing the law against the crime of smuggling shallots, these obstacles were due to the country's vast geography, lack of facilities, lack of personnel, safety of officers, and lack of public awareness of law.